2016
DOI: 10.4103/2249-4863.192333
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric health policy in India: The need for scaling-up implementation

Abstract: In an anticipation of the rising geriatric population in India, the Central government constituted the National Policy for Older Persons in 1999 to promote the health and welfare of senior citizens in India. A major strategy of this policy is to encourage families to take care of their older family members. The policy also encourages voluntary organizations to supplement the care provided by the family and provide care and protection to vulnerable elderly people. The implementation of this policy, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…This period marked the era of broad access to communication technologies like mobile phone and various applications, Internet, E-health and online access to health information [81]. Also during this time, majority of Indian families moved from joint families to nuclear families, and the younger generation migrated to the towns and cities which further weakened the support structures for elderly population, without any signicant improvement in the care and support services for the elderly population [8284].…”
Section: Discussionmentioning
confidence: 99%
“…This period marked the era of broad access to communication technologies like mobile phone and various applications, Internet, E-health and online access to health information [81]. Also during this time, majority of Indian families moved from joint families to nuclear families, and the younger generation migrated to the towns and cities which further weakened the support structures for elderly population, without any signicant improvement in the care and support services for the elderly population [8284].…”
Section: Discussionmentioning
confidence: 99%
“…Based on literature search, it was found that the prevalence of various morbidities among geriatric people in India varies widely from 10% to 80%. (2,16) Considering the minimum prevalence as 10% and 5% absolute margin of error, the sample size was calculated by formula z 2 pq/L 2 . Assuming 10% non-responses, the final sample size came out to be 152.…”
Section: Methodsmentioning
confidence: 99%
“…The family-centered care and support vision for older people is rooted in the Indian tradition that families care for older family members (22). Its appropriateness must be reconsidered in light of the parallel existence of traditional family-based care systems and the growth of 'modern' nuclear family systems in which increasing numbers of older persons receive little informal support (12,13,24,111). This change in family norms and abilities is, however, not clearly addressed in policy.…”
Section: Strengthening the Role Of Primary Mental Healthcare For Older Persons Through Traditional And Existing Resourcesmentioning
confidence: 99%